The Role of Theory in Folkloristics and Comparative Religion - Kamppinen, Matti (The Donner Institute, Åbo Akademi, 2014)
Matti Kamppinen was educated in the philosophy of science and comparative religion. He did his PhD on Amazonian ethnomedicine and folk religion under the supervision of Lauri Honko, and later he studied the cultural models of religion, risk, sustainable development and technology. His books include Cognitive Systems and Cultural Models of Illness (FF Communications 244, 1989), Intentional Systems Theory as a Conceptual Framework for Religious Studies (The Edwin Mellen Press 2010), Methodological Issues in Religious Studies (The Edwin Mellen Press 2012), and The Theory of Culture of Folkorist Lauri Honko (The Edwin Mellen Press 2013, together with Pekka Hakamies). He has published articles in various journals including Futures, the International Journal for Sustainable Society, Corporate Social Responsibility and Environmental Management, Method & Theory in the Study of Religion and Temenos. He is currently working as the Senior Lecturer in Comparative Religion at the University of Turku. He is also Scientific Expert at the Finland Futures Research Centre and Docent at the Department of Theoretical Philosophy, University of Helsinki. Lauri Honko (1932–2002), the Finnish professor of folkloristics and comparative religion was a prolific and multi-talented researcher, whose topics of research ranged from the study of folk beliefs, folk medicine and Ingrian laments to the general theories of culture, identity and meaning. Honko studied Finno-Ugric mythologies, Karelian and Tanzanian folk healing, and South Indian oral traditions. Lauri Honko was known for his originality and theoretical innovations: he constructed multiple approaches to the study of culture that are still relevant in folkloristics and comparative religion. In this paper I aim at explicating and analysing Honko’s views about the roles of theory in folkloristics and comparative religion. More precisely, I will cover two themes. First, I will look at how Honko constructed and utilised theories during the different stages of his career. Second, I ...